2016
DOI: 10.1210/en.2015-1686
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-Specific Disruption of GH Receptor Alters Glucose Homeostasis While Maintaining Normal Cardiac Performance in Adult Male Mice

Abstract: GH is considered necessary for the proper development and maintenance of several tissues, including the heart. Studies conducted in both GH receptor null and bovine GH transgenic mice have demonstrated specific cardiac structural and functional changes. In each of these mouse lines, however, GH-induced signaling is altered systemically, being decreased in GH receptor null mice and increased in bovine GH transgenic mice. Therefore, to clarify the direct effects GH has on cardiac tissue, we developed a tamoxifen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Patients with COPD often show signs of muscle wasting as well as a shift from slow to fast-twitch muscle fibers, therefore, a change in growth hormone receptor expression could be expected [33]. Additionally, mouse models with growth hormone receptor knock-out show similar phenotypes to COPD patients such as impaired glucose tolerance [34], decreased heart function [35], and reduced muscle mass [36]. Growth hormone receptor expression can also decline as people age [37,38], especially after age 60.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COPD often show signs of muscle wasting as well as a shift from slow to fast-twitch muscle fibers, therefore, a change in growth hormone receptor expression could be expected [33]. Additionally, mouse models with growth hormone receptor knock-out show similar phenotypes to COPD patients such as impaired glucose tolerance [34], decreased heart function [35], and reduced muscle mass [36]. Growth hormone receptor expression can also decline as people age [37,38], especially after age 60.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the direct effects of GHR on cardiac tissue, our laboratory generated a tamoxifen-inducible cardiac-specific GHR disrupted (iC-GHRKO) mouse line at 4-month-old (309,310). No difference in baseline or in postdobutamine stress test echocardiography measurements or longitudinal systolic blood pressure measurements were found when compared with controls.…”
Section: Inducible Cardio-specific Ghrkomentioning
confidence: 99%
“…However, alterations in GH signaling are also accompanied by concurrent changes in IGF-1 and insulin levels. This relationship has made it challenging to characterize the independent contribution of GH to aging and diseases of aging, though recent generation of animal models with extrahepatic targeted deletion of GH receptors (GHR) represent a significant step forward in overcoming these limitations to better clarify the role of GH (Jara et al, 2016; List et al, 2015). …”
Section: Gh/igf-1 Axis and Age-related Diseasesmentioning
confidence: 99%
“…On the other hand, Lewis dwarf rats, which have GH and IGF-1 deficiency, have increased incidence of stroke and arterial stress (Csiszar et al, 2008; Ungvari and Csiszar, 2012). However, because these models cannot distinguish from concomitant changes in circulating IGF-1, a model was generated with targeted disruption of GHR in cardiomyocytes (Jara et al, 2016); yet, no alteration in cardiac performance was observed in this model. In contrast, cardiac specific deletion of IGF-1R in adult mice was shown to impair diastolic function, while adult onset IGF-1 deficiency mice demonstrated multiple impairments in cardiovascular function (Bailey-Downs et al, 2012; Li et al, 2008).…”
Section: Gh/igf-1 Axis and Age-related Diseasesmentioning
confidence: 99%